Pengaruh Karakteristik Ibu Terhadap Perkembangan Anak di Posyandu Mawar II Desa Pasir Gombong Kab. Bekasi Tahun 2018 - Temmy Lanovia Anggraini; Sofie Handajany (UP3M AKPER-AKBID BHAKTI HUSADA CIKARANG, 2019)
Child development is a matter that requires special attention. Assessment of children's development is important to do early detection of developmental disorders. This research was conducted with the aim to determine the effect of maternal characteristics on the development of children. Variable characteristics of mothers include age, education and occupation. Assessment of children's development using the Pre Development Screening Questionnaire (PDSQ). Aspects of development assessed include gross motor, fine motor, socialization and independence, speech and language. This study is a descriptive analytic study using a cross sectional approach. The study was conducted in August 2018 at the posyandu Mawar II in the village of Pasir Gombong, Bekasi Regency. The sampling technique uses purposive sampling. The research subjects were 44 children with a range of 0 - 72 months of age. Data analysis using Fisher Exact test. The results of the development assessment found 40 respondents (90.9%) had a level of development in accordance with their age and as many as 4 respondents (9.1%) had a doubtful level of development. From the Fisher Exact test results for each of the three variables each obtained p = 1,000 (> 0.05) so that it can be concluded there is no relationship between maternal age and child development, there is no relationship between maternal education and child development and there is no relationship between maternal work with child development.